2022
DOI: 10.1038/s42003-022-04168-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide analysis of Taiwan Biobank reveals novel glycemia-related loci and genetic risks for diabetes

Abstract: To explore the complex genetic architecture of common diseases and traits, we conducted comprehensive PheWAS of ten diseases and 34 quantitative traits in the community-based Taiwan Biobank (TWB). We identified 995 significantly associated loci with 135 novel loci specific to Taiwanese population. Further analyses highlighted the genetic pleiotropy of loci related to complex disease and associated quantitative traits. Extensive analysis on glycaemic phenotypes (T2D, fasting glucose and HbA1c) was performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In our joint analysis, we also found that wPRS T2D was significantly associated with TG and LDL-C. As Lee et al. 35 estimated, diabetes showed significant genetic correlations with TG and LDL-C ( r g = 0.42 and 0.19, respectively) in the Taiwan population, 35 suggesting that T2D shares genetic components with lipid traits. Studies have established a causal relationship of T2D on lipid traits using Mendelian randomization, where T2D genes were used as instrumental variables.…”
Section: Discussionsupporting
confidence: 69%
“…In our joint analysis, we also found that wPRS T2D was significantly associated with TG and LDL-C. As Lee et al. 35 estimated, diabetes showed significant genetic correlations with TG and LDL-C ( r g = 0.42 and 0.19, respectively) in the Taiwan population, 35 suggesting that T2D shares genetic components with lipid traits. Studies have established a causal relationship of T2D on lipid traits using Mendelian randomization, where T2D genes were used as instrumental variables.…”
Section: Discussionsupporting
confidence: 69%
“…An early study reported that in the US population, vitamin A and CR were positively correlated with each other 51 , while CR was associated with GCKR 11,52 . Several studies have shown that higher magnesium levels were associated with lower risk of hyperuricaemia 53,54 , while urine acid had significant gene DNAJC16 27,55 . The plots for visualizing genetic colocalization analysis of two GWAS results from this study and the companion works were provided in Figure 6 and Supplementary Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that chromosome 16p13.3 as a gene locus is associated with erythrocyte traits ( Kichaev et al, 2019 ; Vuckovic et al, 2020 ; Sinnott-Armstrong et al, 2021 ). By including TWB participants in their study, Lee et al (2022) revealed that the PGAP6 rs375498857 genotype is associated with several RBC traits. In our study, we observed that NPRL3 rs191086839, LUC7L rs372755452, and PGAP6 rs375498857 are associated with multiple erythrocyte indices, exhibit strong LD, and are specific to the Asian population.…”
Section: Discussionmentioning
confidence: 99%